Effects of moisture on the bonding performance of asphalt-aggregate system. (9th August 2021) - Cong, Peiliang; Guo, Xize; Ge, Wanshuai
Graphical abstract: Highlights: Failure mode changed from cohesive failure to adhesive failure with the duration of moisture conditioning. Aromatic and saturated weakened the interaction between polar components and aggregate. Moisture resistance of asphalt-aggregate system increased with the rise of resin content. Abstract: Water molecules will damage the bonding performance of asphalt-aggregate system, which will seriously affect the durability of asphalt pavement. The asphalt-aggregate system were prepared using three asphalt types (SBS modified asphalt binder (SBSMA), base asphalt (SK70 and SK90)) and three aggregates (granite, diabase and limestone) with different mineral composition. Tensile tests were performed on aggregate-asphalt samples under different moisture conditioning time. It was found that the continuous moisture conditioning caused the failure mode of samples to transform from cohesive to adhesion. The time point at which the failure mode starts to change can be used to characterize the moisture sensitivity of asphalt-aggregate system. The correlation between image structure of fracture surfaces and adhesion loss was verified through collecting and processing photos of the fracture surface. In addition, the effects of microscopic indices (fraction content of asphalt binder, structural index of asphalt binder and element content of aggregate) on the moisture sensitivity of the asphalt-aggregate system were quantified. The results showed that fractions of the asphalt binder had a more significant influence on the moisture sensitivity than elements ( Si, Ca ) of the aggregate. The rise in resin content would increase the moisture resistance of the asphalt-aggregate system.